Outdoor workers’ sun-related knowledge, attitudes and protective behaviours: a systematic review of cross-sectional and interventional studies - Reinau, Daphne; Weiß, Melanie; Diepgen, Thomas L. (British journal of dermatology, 2013)
Sun protection is a major concern for outdoor workers as they are particularly exposed to solar ultraviolet radiation and therefore at increased risk of developing some forms of skin cancer, cataract and ocular neoplasm. In order to provide an overview of outdoor workers’ sun-related knowledge, attitudes and protective behaviours as reported in the literature and to evaluate the effectiveness of sun-safety education programmes in outdoor occupational settings, we conducted a systematic review of the literature by searching three electronic databases (PubMed, Embase, PsycINFO) from their inception up to 25 April 2012. An extensive hand search complemented the database searches. We identified 34 relevant articles on descriptive studies and 18 articles on interventional studies. Considerable numbers of outdoor workers were found to have sun-sensitive skin types; sunburn rates per season ranged from 50% to 80%. Data concerning outdoor workers’ sun-related knowledge and attitudes were scarce and controversial. The reported sun-protective behaviours were largely inadequate, with many workers stating that they never or only rarely wore a long-sleeved shirt (50-80%), sun-protective headgear (30-80%) and sunscreen (30-100%) while working in the sun. However, there is growing evidence that occupational sun-safety education is effective in increasing outdoor workers’ sun-protection habits and presumably in decreasing sunburn rates. Occupational sun-safety education programmes offer great potential for improving outdoor workers’ largely insufficient sun-protective behaviours. It is hoped that, in the future, committed support from healthcare authorities, cancer foundations, employers and dermatologists will open the way for rapid and uncomplicated implementation of sun-safety education programmes.
First published: 18 December 2012
Gesehen am 07.05.2018